Determination of Corrosion, Noise and Vibration Characteristics of a Multifunctional Epoxyurethane-Based Coating for Transport and Technological Machines - Dastamovich, Ibragimov Botir (INTERNATIONAL CONFERENCE ON MULTIDISCIPLINARY RESEARCH AND INNOVATIVE TECHNOLOGIES, 2021)
The article examines the issues of determining the characteristics of an anticorrosive coating based on epoxyurethane for transport and technological machines. Vehicles are constantly exposed to corrosion processes, and the durability of metal parts depends on the intensity of corrosion. This indicates the need for research and the importance of scientific and technical work in this area. In laboratory conditions, on the basis of local raw materials, an anticorrosive coating was synthesized - epoxyurethane with an additive. Corrosion protection was determined by the method of weight loss of metal plates in various aggressive environments, adhesion and degree of protection against corrosion, as well as the influence of noise and vibration.